-4(8p-7)-p=106

Simple and best practice solution for -4(8p-7)-p=106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(8p-7)-p=106 equation:


Simplifying
-4(8p + -7) + -1p = 106

Reorder the terms:
-4(-7 + 8p) + -1p = 106
(-7 * -4 + 8p * -4) + -1p = 106
(28 + -32p) + -1p = 106

Combine like terms: -32p + -1p = -33p
28 + -33p = 106

Solving
28 + -33p = 106

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-28' to each side of the equation.
28 + -28 + -33p = 106 + -28

Combine like terms: 28 + -28 = 0
0 + -33p = 106 + -28
-33p = 106 + -28

Combine like terms: 106 + -28 = 78
-33p = 78

Divide each side by '-33'.
p = -2.363636364

Simplifying
p = -2.363636364

See similar equations:

| r-9.1=-9.8 | | w+(-2)=-18forw | | 238=7(7b-1) | | -138=6(4n-3) | | n+8=n+2 | | 14+4n=8n-3(n-6) | | 5(5+2x)=105 | | 3x-y=37 | | 3ln(x-1)=15 | | 0.10x+0.10y=100 | | 1/6(x+4)=3x-4(2-x)-5 | | -114=6(-4+2a)+6a | | -9x-y=-59 | | 58-7x=11x+24 | | 2/5(2x+11)=3(4-3x)+12 | | 2/5x^2+1/5x-2=0 | | -6(1-6r)=138 | | 2/5(2x+11)=3(4x-3x)+12 | | -152=4(4k-6) | | -5n+18+3n=-6 | | n=2-3 | | -107=r+3(7r+1) | | 24x+19x= | | 8(h+3)=7(h-3) | | 25x^5y^3/50x^2y^7 | | 15m+23=-7m+18 | | -9+6v=v-5+6v | | 2X/4+3X/9 | | 2X/4+3X/9+4X/16+5X/25 | | 5a-6b-2a+3b= | | -q-13=2q+5 | | -1+3p=-1p-5p |

Equations solver categories